Knowledge and pacification on the U.S. conquest and the writing of Philippine history - Ariate, Joel F., Jr. (2018)
Access online through this link: https://journals.upd.edu.ph/index.php/kasarinlan/article/view/7071/6156
Keywords: Philippine-American War, 1899-1902; Books -- Reviews; Ileto, Reynaldo C